Tinjauan Limbah Cair Mall Jambi Town Square PT. Temas Alvindo Jambi - Guntar Marolop Saragih (Jurnal Daur Lingkungan, 2018)
Mall of Jambi Town Square (Jamtos) PT. Temas Alvindo uses Biofilter Anaerob-Aerob to do treatment for its wastewater used consisting of 1. Inlet (grease trap); 2. Primary basin; 3. Sludge basin; 4. Equalization tank; 5. Polishing;  6. Biodetox; 7. Clarifier basin; 8. Clorination; 9. Effluent. This installation capacity for wastewater is 120 m3 per day, meanwhile total of wastewater from its activities in a day is 43 m3. Some parameters of wastewater in inlet which is still above the limit concentration of standard regulation were BOD5 804 mg/L; COD 2.078 mg/L; TSS 479 mg/L and Total Coliform 4.100. The parameters concentration of outlet does not meet the threshold limit value in standard regulation, which were BOD 423 mg/L; COD 1.054 mg/L; TSS 32 mg/L and Total Coliform 3.100. However, oil and grease; ammonium and pH were below the threshold limit value.